Purifying the consciousness in Hebrews cult, defilement and the perpetual heavenly blood of Jesus - Bloor, Joshua D. A. (London Bloomsbury Publishing Plc, 2023)
Cover -- Halftitle page -- Title page -- Copyright page -- Contents -- Tables -- Acknowledgements -- Abbreviations -- 1 Introduction -- 1.1 The statement of the problem -- 1.2 The situation of the recipients -- 1.3 Συνείδησις: An overview24 -- 1.3.1 An interpretative history -- 1.3.2 Ancient Greek origins -- 1.3.3 The Jewish Scriptures -- 1.3.4 Philo -- 1.3.5 Josephus -- 1.3.6 New Testament -- 1.4 Συνείδησις in Hebrews -- 1.4.1 Defining συνείδησις in Hebrews -- 1.4.2 The application of συνείδησις in Hebrews scholarship -- 1.5 Methodological approach -- 1.6 Outline of the study -- Part One The defiled consciousness -- 2 Cosmic defilement: The cultic context of defilement -- 2.1 Introduction -- 2.2 The present problem -- 2.3 Defilement in the cultic sphere -- 2.3.1 Dorian Gray and impurity in the cultic sphere -- 2.3.2 Moral and ritual impurity -- 2.3.3 The reality of defilement -- 2.4 The heavenly tabernacle in Hebrews -- 2.4.1 Hebrews and cosmology -- 2.4.2 Construing the architecture of the heavenly tabernacle67 -- 2.4.3 Earthly and heavenly tabernacle terminology -- 2.4.4 The absence of temple terminology -- 2.4.5 The 'sketch' and 'foreshadow' -- 2.5 Defilement in Hebrews -- 2.5.1 Introducing sin in Hebrews -- 2.5.2 Moral and ritual impurity? -- 2.5.3 Sin as conscious defilement (συνείδησις) in Hebrews -- 2.5.4 'Dead works' -- 2.5.5 Types of sin? Unintentional/intentional sin -- 2.5.6 Defiled heavenly tabernacle -- 2.6 The effects of a defiled συνείδησις -- 2.6.1 Restricted access -- 2.6.2 The stain, dread and timidity of defilement -- 2.6.3 Apostasy, rebellion and the wilderness motif -- 2.7 Conclusion -- Part Two Purifying the consciousness: Cosmic purgation -- 3 Navigating Hebrews' sacrificial argumentation: Yom Kippur and Jesus' earthly and heavenly achievements -- 3.1 Introduction -- 3.2 Navigating scholarship -- 3.2.1 Critiquing Moffitt.
Description based on publisher supplied metadata and other sources
Keywords: Sacrifice-Christianity-History of doctrines; Sin-Biblical teaching; Electronic books; Hochschulschrift